2014
DOI: 10.1152/ajplung.00319.2013
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosaflagellar motility activates the phagocyte PI3K/Akt pathway to induce phagocytic engulfment

Abstract: Lovewell RR, Hayes SM, O'Toole GA, Berwin B. Pseudomonas aeruginosa flagellar motility activates the phagocyte PI3K/Akt pathway to induce phagocytic engulfment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…PA strains isolated from CF patients with chronic infections are often non-motile, lacking flagellin and pilin, whilst environmental isolates and isolates obtained during early colonization are motile (Luzar et al, 1985). These non-motile strains are also resistant to phagocytosis by macrophages (Lovewell et al, 2014; Luzar et al, 1985). In contrast, non-CF mucus has been shown in vitro to inhibit adhesion and the subsequent loss of motility (Yeung et al, 2012).…”
Section: Respiratory Tract Mucusmentioning
confidence: 99%
“…PA strains isolated from CF patients with chronic infections are often non-motile, lacking flagellin and pilin, whilst environmental isolates and isolates obtained during early colonization are motile (Luzar et al, 1985). These non-motile strains are also resistant to phagocytosis by macrophages (Lovewell et al, 2014; Luzar et al, 1985). In contrast, non-CF mucus has been shown in vitro to inhibit adhesion and the subsequent loss of motility (Yeung et al, 2012).…”
Section: Respiratory Tract Mucusmentioning
confidence: 99%
“…Bacterial motility is a key phenomenon essential for adhesion and colonization, ultimately 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 advantage [34][35][36][37] . Recently, Hamblett et al 38 using a large set of CF isolates of P. aeruginosa showed that pulmonary exacerbation correlated well with reduced twitching motility of the bacterium.…”
Section: Cf Strains Have Decreased Motility and Adhesion Compared To mentioning
confidence: 99%
“…Previous data demonstrated that the PI3K/Akt pathway, which is an important mammalian intracellular signaling pathway for phagocytosis of many bacteria by host cells, is activated in response to motile bacteria but not by non-motile bacteria [32, 37]. Relative Akt activation was quantitatively measured by FACS analysis following intracellular staining for phosphorylated Akt (phospho-Akt).…”
Section: Resultsmentioning
confidence: 99%
“…The phenotypic assay for swimming motility was performed as previously described in 0.3% LB agar plates [21, 32]. Images were collected at 48-h post inoculation to monitor the formation of bacterial halos to assess the relative swimming motilities of the bacterial strains.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation